TRANSFORMATIONAL LEADERSHIP OF SCHOOL ADMINISTRATORS AFFECTING MORALE IN WORKING OF TEACHERS UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Kammakan, Chanokchon; Klinmalee, Rattaporn; Chatakan, Werayut (Journal of MCU Nakhondhat, 2023)
The purposes of this research were to study Transformational Leadership of School Administrators, to study morale in working of teachers, to study Transformational Leadership of School Administrators affecting Morale in working of teachers and to propose the approaches of developing the guideline of transformational leadership of School Administrators under the Primary Educational Service Area Office 1. The research samples included 306 teachers under Nakhon Si Thammarat Educational Service Area Office 1. The data collection instrument were questionnaires and interviewing for research. The research findings were as follow: 1. Transformational Leadership of School Administrators under Nakhon Si Thammarat Primary Educational Service Area Office 1 are highest in overall view. 2. Morale in working of teachers under Nakhon Si Thammarat Primary Educational Service Area Office 1 are highest in overall view. 3. Transformational Leadership of School Administrators affecting Morale in working of teachers under Nakhon Si Thammarat Primary Educational Service Area Office 1. in overall view, The relationship were moderate (r = .64**). there were statistical significant relationship at 0.05 by executive transformational leadership in terms of Inspiration motivation organizational communication and Individualized consideration had a positive effect on the morale of teachers under Nakhon Si Thammarat Primary Educational Service Area Office 1. 4. propose the approaches of developing the guideline of transformational leadership of School Administrators under the Primary Educational Service Area Office 1. Should focus each aspect as follows: 1) Idealized influence aspect should encourage the pride and confidence in working. 2) Individualized consideration aspect should always urge all staff for their self-development according to their potentiality. 3) Inspiration motivation aspect should promote the good attitude in working. And 4) organizational communication aspect should use communication methods to create mutual understanding.